Representação discursiva da deficiência visual em documentos norteadores da educação especial e em objetos de ensino de língua portuguesa - Gonzaga, Camila da Silva (2023)
This doctoral thesis focuses on the discursive representation of the inclusion of students with visual impairments and visual impairments themselves in guiding documents for special education and teaching materials for Portuguese language instruction. Despite the existence of Decree No. 21/2012, which was established through Federal Law No. 10.753/2003, establishing the National Book Policy and ensuring access to reading for People with Visual Disabilities, and Decree No. 7.084/2010, Article 28, which mandates that the Ministry of Education, through the educational material program, ensures accessibility for the target audience and their teachers, it seems that the law's guarantee is not happening in the current context in educational institutions for students with visual impairments, as not all educational materials arrive at schools with adaptations in Braille or audio descriptions (Fernandes, 2007). Furthermore, inclusion is still seen in a way that does not account for differences in students' learning. Thus, there is the identification of a social problem involving People with Disabilities, constructed by various barriers that hinder accessibility. With this in mind, the research has the following general objective: To investigate if and to what extent the National Common Curricular Base (BNCC) for High School, the National Textbook Program (PNLD/2021), the New High School (NEM) (through Law 13.415/17), and some Portuguese Language textbooks for High School address accessibility to critical reading for students with visual disabilities and identify how and which model of disability and inclusion are discursively represented in these documents. The specific objectives are as follows: 1) Identify what is proposed regarding accessibility and the inclusion of students with visual impairments in PNLD/2021, the High School Reform, and the BNCC for High School, how producers engage with the topic, and to what extent these documents promote accessibility to critical reading for students with visual impairments, considering the constitutive multimodality of texts. 2) Examine if High School Portuguese Language textbooks respond to what is proposed in these documents regarding the inclusion of students with visual impairments, if these textbooks propose readings that encompass multimodality, facilitate accessibility for students with visual impairments, and which model of disability the activities proposed in the analyzed educational materials are related to. To achieve the objectives, the research is primarily based on the following theoretical and methodological assumptions: Critical Discourse Analysis (CDA), specifically the dialectical-relational approach (Fairclough, 2001, 2003; Chouliaraki; Fairclough, 1999); studies on multimodality (Hodge; Kress 1988; Kress; Van Leeuwen, 2001); the Social Theory of Disability (Hunt, 1966; Oliver, 1983); accessibility and inclusion, specifically the inclusion of people with visual disabilities or blindness (Sassaki, 2006; Diniz, 2012, Mantoan, 2003; Mazzota, 2003, 2008, 2013; Lima, 2018; Lima; Magalhães, 2018). The research has a qualitative approach and uses data collection techniques through bibliographic research and documentary research. The results indicate that students with visual disabilities are discursively represented as incapable (ableism). Regarding the inclusion of students with visual disabilities, it is discursively represented, as observed in the analyzed documents, still based on an Individual Medical Model of disability. Furthermore, it was found that these students face various accessibility barriers, even with all the advances in technology, and that the voices and texts that make up guiding documents for basic education give little importance to Specialized Educational Assistance.